Penerapan Model Non-Directive Learning Berbasis Kurikulum Merdeka untuk Meningkatkan Kemandirian Peserta Didik pada Pembelajaran Tari - Santosa, Meisya Putri Fujiningtyas; Budiman, Agus; Sabaria, Ria (Global Action and Education for Society, 2026)
This research is motivated by the low level of student independence at SMP Pasundan 3 Bandung, prompting the use of the Non-Directive Learning model based on the Merdeka Curriculum as an alternative solution to this problem. The main objective is to examine the effectiveness of the Non-Directive Learning model in dance education to enhance student independence. A quantitative approach was used in this study, employing a pre-experimental design with a one-group pretest-posttest model. The study involved 41 students from class VIII A (21 boys and 20 girls). Data were collected through questionnaires, observations, interviews, and documentation. The data analysis included tests of instrument validity and reliability, descriptive statistics, normality testing, and hypothesis testing (t-test). The results indicate that the Non-Directive Learning model had a positive impact on improving student independence. The hypothesis test (paired sample t-test) yielded a significance value of 0.000 < 0.05, indicating a significant difference between the pretest (mean score: 66) and posttest (mean score: 80). This improvement confirms that the implementation of the Non-Directive Learning model effectively enhances student independence.